Modelling the Relationship between Urban Environment and Travel Behaviour: Policy and Indicators. - Paix, Lissy La; Monzón, Andrés; Cherchi, Elisabetta (My University, 2013)
Due to the necessity to undertake activities, every year people increase their standards of travelling (distance and time). Urban sprawl development plays an important role in these "enlargements". Thus, governments invest money in an exhaustive search for solutions to high levels of congestion and car-trips. The complex relationship between urban environment and travel behaviour has been studied in a number of cases. Thus, the objective of this paper is to answer the important question of which land-use attributes influence which dimensions of travel behaviour, and to verify to what extent specific urban planning measures affect the individual decision process, by exhaustive statistical and systematic tests. This paper found that a crucial issue in the analysis of the relationship between the built environment and travel behaviour is the definition of indicators. As such, we recommend a feasible list of indicators to analyze this relationship.
Keywords: Verkehr; Region; Stadtumland; Metropolregion; Zersiedlung; Verkehrsentwicklung; Modellierung; Urban Sprawl